PENGGUNAAN STRATEGI PQ4R BERBANTUAN PETA KONSEP DALAM MEMBACA PEMAHAMAN TEKS CERITA PENDEK SESUAI GAYA KOGNITIF SISWA - Prasetyo Adi Wibowo; Dawud Dawud; Endah Tri Priyatni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
Teaching reading comprehension of short stories needs particular strategy and knowledge of students’ cognitive styles. One of the strategies to teach reading comprehension of short stories is PQ4R integrated with concept mapping. There are two types of students’ cognitive styles, field dependent and field independent. This research is aimed to investigating the effect of PQ4R integrated with concept mapping strategy, the effect of the students’ cognitive styles and the interaction of both on reading comprehension ability of the seventh grade students of Junior High School 3 Malang. It is a quantitative research. Data generated in the form of test scores were analyzed using Ancova test.